Role of Decision Making Process of Farm Women Regarding Vegetable Operation - Singh, D.K.; Thakur , Pramod Singh; Singh, Deepmala; Kumar, Anjani (Indian Journal of Extension Education, 2015)
Decision making is the process of consciously choosing courses of action from available alternatives and integration of  them for the purpose of achieving the desired goal. Farm women are participated in most of the important agricultural  operations like field preparation, sowing of seed, planting of seedlings inter-cultivation, weeding and plant protection  measures, picking & harvesting, compost making application of manures and fertilizers, cleaning of farm products. In  vegetable cultivation, decision making always remained associated with the farm women utilization relating to various  aspects in the study area, yet their involvement in this process has not been recognized. It was evident from vegetable  cultivation, the joint decisions by male and female partners of the household are important. The present study was  conducted in Panagar block of Jabalpur district. A list of vegetables growing villages was prepared with the help of  extension official out of these only 5 villages were selected randomly due to major vegetable growing area. A representative sample of 110 vegetable growers was drawn from the selected villages. During the research study, it was  observed that majority of farm women had always taken decision regarding selection of crop, quantity of seed, sowing  time of seed, weeding, use of manures, harvesting, picking and seed storage. They were rarely involved in decision  making regarding nursery management, field preparation, selection of variety, irrigation, seed treatment and marketing  and use of fertilizers, plant protection measures as it required more scientific knowledge and skill.
Keywords: Decision making; farm women; vegetable operation